Analysis of A Tall Structure Considering Base Isolators Using ETABS - Patil, Shravan Kumar Sahu; Patil, Pradeep Kumar; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2024)
Safety of people in a building depends on capability of the building to resist earthquake waves and then stands upright after earthquake situation without or with few damages and maintenance. Various systems like dampers, base isolators, shear wall, elevated water tank, etc., are use to dissipate seismic energy. Effectiveness of these systems is based on its type and position of these elements. In this research paper, seismic analysis of G+16 storey residential structure is studied based on storey shear and overturning moment by Time History Analysis. Time history data is obtained from PEER Ground Motion Database.